Strategi Pembudayaan Technopreneur Menuju Madrasah Hebat di MAN 2 Kulon Progo - Anita Isdarmini (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This Best Practice aims to describe the implementation of Madrasah Technopreneur so that it is able to save MAN 2 Kulon Progo. This innovation is backed by the challenges of Madrasah that must be faced namely the low education and economic parents of the students of MAN 2 Kulon Progo, and graduates of Madrasah who choose to work. The strategic step in making Madrasah Technopreneur is to build a joint commitment of stakeholders, revitalization, compose academic script, launch tagline